Tea Fermentation of A. malacencis with Lactobacillus plantarum as a starter : Total Phenol Content, Total Flavonoids Content And Antioxidant Activity, In vitro study as a functional drink - Sari, Rafika; Apridamayanti, Pratiwi (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Some herbal teas contain antioxidant compounds that neutralize the free radicals involved in ageing processes and various diseases. Fermentation can increase the antioxidant activity in herbal teas due to the metabolic outputs of the microorganisms involved in the fermentation process. Aquilaria malaccencis is used to make teas in Indonesia and other countries and has been identified as demonstrating antioxidant properties. This study aimed to determine the characteristics of tea made from A. malaccencis leaves and fermented with Lactobacillus plantarum for 48 hours, 96 hours and 192 hours. The features investigated were antioxidant activity measured via DPPH assay and total phenol and flavonoid content measured spectrophotometrically. The fermentation results at 48, 96 and 192 hours were a pale yellow, sour aroma and sour taste and total lactic acid bacteria (LAB) content of 8.49 x 106 CFU/mL, 7.42 x 106 CFU/mL and 2.6 x 1010 CFU/mL, respectively. Antioxidant activity (IC50) at 48 hours was 439.444 µg/ml, at 96 hours was 235.309 µg/ml, and at 192 hours was 190.33 µg/ml. Total phenolic content (mg/g GAE) at 48 hours was 22.561, at 96 hours was 18.173, and at 192 hours was 21.14. Total flavonoid content (mg/g QE) at 48 hours was 1.901, at 96 hours was 1.938, and at 192 hours was 3.76. This research concluded that Lactobacillus plantarum as a starter for fermented tea made from Aquilaria malaccensis Lam. (A. malaccensis) leaves could produce appropriate characteristics for its functional food consumption. The best fermentation time was 192 hours, delivering an IC50 value of 190.33 ± 1.64 µg/ml, total phenol content of 36.346 mg/g GAE, and total flavonoid content of 3.876 ± 0.317 mg/g QE.Keywords: Tea fermentation, antioxidant activity, total phenolic content, total flavonoid content.